(untitled) (Global Journal of Management and Business Research, 2021)
The development concern Application issues in post-COVID-19 Africa and the planet are wounding through a litany of scholarship scholarships. Many scholars in Africa and the world, in general, are genuinely interested, and indeed sometimes brain-storm, on what needs to be done by a wide variety of scholars, including but not limited to scientists, economists, sociologists, psychologists, theologians, experts, and finance studies. This examined the characteristics and financial performance of the listed conglomerate companies in Nigeria. The research work has adopted a descriptive design to determine the reciprocal relationship between variables. Data were collected mainly from secondary sources via the published annual reports of the sampled companies for the period 2010-2018 they were analyzed using multiple regression techniques after carrying out a series of robustness tests to determine their validity. The results of the study showed that the size of the business had a positive and significant impact on financial performance. On the other hand, leverage negatively, but insignificantly, on financial results. The study indicates that management should maximize the total amount of assets as much as possible, as this is a guarantor of future economic benefits.